Konseling Teman Sebaya dengan Seni Kreatif Berbasis Kearifan Lokal untuk Meningkatkan Resiliensi Remaja Sekolah Menengah Pertama - Prasetiawan, Hardi; Wahyudi, Amien; Fauziah, Mufied (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2022)
This study aims to guide the implementation of Peer Counseling with Creative Arts based on local wisdom to increase resilience. The method used is development research. The instrument used is a scale using 2 forms, namely Scale I & Scale II. The results according tothis study clearly explain the application of Peer Counseling with Creative Arts based on Local Wisdom.